2019
DOI: 10.1111/gcb.14784
|View full text |Cite
|
Sign up to set email alerts
|

Nearshore coral growth declining on the Mesoamerican Barrier Reef System

Abstract: Anthropogenic global change and local stressors are impacting coral growth and survival worldwide, altering the structure and function of coral reef ecosystems. Here, we show that skeletal extension rates of nearshore colonies of two abundant and widespread Caribbean corals (Siderastrea siderea, Pseudodiploria strigosa) declined across the Belize Mesoamerican Barrier Reef System (MBRS) over the past century, while offshore coral conspecifics exhibited relatively stable extension rates over the same temporal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 78 publications
(157 reference statements)
2
22
0
Order By: Relevance
“…Additionally, mid- and outer-shelf reefs have been less sensitive to heat stress than those nearshore, with evidence of only minor bleaching events in the skeletal cores and no apparent increase in frequency or severity in recent decades. A similar pattern of highly susceptible nearshore corals and more resilient offshore corals has been reported in the Mesoamerican reef system ( Baumann et al, 2019 ). As sea surface temperatures increase in the coming decades, the central Red Sea will be subjected to more frequent and intense heat stress events ( Cantin et al, 2010 ; Van Hooidonk, Maynard & Planes, 2013 ; Hoegh-Guldberg et al, 2014 ).…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, mid- and outer-shelf reefs have been less sensitive to heat stress than those nearshore, with evidence of only minor bleaching events in the skeletal cores and no apparent increase in frequency or severity in recent decades. A similar pattern of highly susceptible nearshore corals and more resilient offshore corals has been reported in the Mesoamerican reef system ( Baumann et al, 2019 ). As sea surface temperatures increase in the coming decades, the central Red Sea will be subjected to more frequent and intense heat stress events ( Cantin et al, 2010 ; Van Hooidonk, Maynard & Planes, 2013 ; Hoegh-Guldberg et al, 2014 ).…”
Section: Discussionsupporting
confidence: 79%
“…Yet, this is not a universal trend (e.g., Cooper et al., 2012; Kuffner et al., 2019; Manzello et al., 2015), suggesting that the severity of the calcification rate decline depends on the thermal sensitivity of each species (Carricart‐Ganivet et al., 2012; Goffredo et al., 2009) and the reef area inhabited by the coral colonies (Castillo et al., 2011). In the Western Caribbean, it has been shown that some coral species (e.g., Orbicella spp., Porites astreoides , Dichocoenia stokesi , Dendrogyra cylindrus , Siderastrea siderea , and Pseudodiploria strigosa ) have reduced calcification rates due to increases in ocean temperature, ocean acidification, and anthropogenic pressures (Baumann et al., 2019; Carricart‐Ganivet et al., 2012; Castillo et al., 2011; Cruz‐Ortega et al., 2020). In this context, the use of a single calcification estimate for each species in our approach may have resulted in an over‐estimation if calcification decreased in response to warming over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Individual cores and density standards were visualized as the mean voxel intensity of a~3.00 mm thick digital slice using standardized window widths and window levels in the software Horos (version 2.4.1) and exported as an image for measuring growth rates in Coral XDS [51]. To quantify density from CT image intensity following established methods [52][53][54][55], linear models between known density and CT intensity of the density reference materials for three independent scans were derived using the function lm in the statistical package R version 4.0.2 [56]. Transects were analyzed along the major growth axis of individual polyps to quantify mean extension and intensity of subsequent high and low intensity bands using the half range mode and converted to skeletal density using the density calibration curves for each scan.…”
Section: Quantification Of Linear Extension Skeletal Density and Camentioning
confidence: 99%
“…Linear mixed effects modeling was used to detect the fixed effects of winter NAO index, species, site, and the interactions between the winter NAO index and species or site on annual calcification rates for the duration of the NAO index (i.e., 1950-2015) using the R package nlme [62]. This analytical approach was used to account for nesting of calcification rates within each core and data imbalances generated by variable lengths of core time series data with the capacity to detect small trends in coral calcification rates following established methods [53,55,63]. Briefly, each coral core was treated as an individual sampling unit with annual calcification rates nested within each core.…”
Section: Linear Mixed Effects Modelingmentioning
confidence: 99%